Occurrence characteristics of ash-forming elements in sea rice waste and their effects on particulate matter emission during combustion. (1st August 2020) - Li, Xiaomin; Gong, Xun; Zhang, Chuxuan; Liu, Tingfeng; Wang, Wenyu; Zhang, Yang
Graphical abstract: Highlights: PM emission from combustion of sea rice waste was firstly investigated. Sea rice husk has more Na and Cl, less K. Combustion of sea rice waste generated more PM10 . Abstract: Sea rice is a strategic resource which will play an important role in global food supply, especially in the context of rapid population growth and the associated reduction in agricultural land areas, freshwater shortage, and sea-level rise as a result of global warming. This study investigates the occurrence characteristics of ash-forming elements in sea rice waste (including sea rice straw and sea rice husk) and their effects on thermal behavior and particulate matter emissions during combustion. The results show that sea rice waste has more Na, Mg and Ca than ordinary rice waste. The Na content in sea rice straw is 1643 mg/kg_fuel, whereas that in ordinary rice straw is only 380 mg/kg_fuel, and sea rice husk contains approximately 30 times more Na than ordinary rice husk. Sea rice husk also has a lower K content, which increases its thermal stability. Furthermore, maximum of decomposition rates occur at about 301 °C which is a higher temperature than that for ordinary rice husk (290 °C). Sea rice waste combustion was conducted in a high-temperature drop tube furnace at 1500 °C. Results show that sea rice waste combustion released more PM10 than ordinary rice waste, and the oxy-fuel atmosphere promoted the formation of PM10 .